The effectiveness of Google classroom from the perspective of students in the fourth stage of physical education teaching methods - Subhi Ibrahim, Hayder; Hameed Wadi, Hiba (International Journal of Psychosocial Rehabilitation, 2020)
The digital world is now the clear feature of this era, especially with the development of life and the increasing use of technology tools and programs from the youth category in particular, which made the trend towards the electronic field a must in all fields, especially the field of education, and it was to introduce electronic education in our educational systems Different reactions between the segments that benefit from it, namely the teaching staff and students in particular, and with most of Iraq’s universities heading towards various electronic platforms, including the Google workplace platform, many students and professors alike faced some difficulties, so the researcher decided to know the perception of students of the College of Physical Education - University of Diyala About the use of the Google Classroom platform. The researcher used the descriptive approach for its relevance and nature of the research and used the questionnaire as a tool to measure students' perception of using Google Classroom. The research sample and community consisted of students of the College of Physical Education and Sports Sciences - University of Diyala. After distributing the questionnaire and discussing the results, it appeared that the students' perception was positive in some axes related to the flexibility of use in terms of timing, answering assignments, and performing exams, and students have some negative perceptions about the steps to activate e-mail and use it.